The real world impact of adalimumab on quality of life and the physical and psychological effects of moderate-to-severe psoriasis: a UK prospective, multicenter, observational study. (2nd April 2020) - Leman, Joyce; Walton, Shernaz; Layton, Alison M.; Ward, Kathleen A.; McBride, Sandy; Cliff, Sandeep; Downs, Anthony; Landeira, Margarita; Bewley, Anthony
Abstract: Psoriasis can adversely affect quality of life (QoL) and emotional well-being. In this UK prospective observational study we evaluated the 'real-world' impact of adalimumab on QoL and the physical/psychological effects of moderate-to-severe psoriasis. Hundred and forty-three biologic-naïve patients with moderate-to-severe psoriasis, receiving adalimumab in clinical practice, were included. Patients completed a series of questionnaires at baseline (adalimumab initiation), 4 and 16-weeks and 6-months post-adalimumab initiation during routine visits. The main outcome measure was the proportion of Dermatology Life Quality Index (DLQI) 'responders' at 16 weeks, defined as ≥5 point reduction from baseline or DLQI = 0.90% (95% CI = 80.8%–94.6%) of evaluable patients were DLQI responders at 16-weeks. There were significant improvements at 16 weeks in patient-reported measures of QoL, mental and physical well-being, cutaneous body image, anxiety, depression and psoriasis severity, which were maintained at 6-months. Adalimumab treatment was associated with improvements in patients' QoL and psychological functioning, which occurred contemporaneously with improvements in cutaneous disease.